Listen, nature is talking to us - Abd Razak, Dzulkifli (2008)
Four years ago, we read about freak incidents where crustaceans, fish and other marine animals landed in abundance on our shores and those of our neighbours. To most these signalled some sort of blessing from heaven. Little did they know that they were actually signs of impending disaster. In this case, it was the tsunami of December 2004, which hit not only Aceh, but a dozen other countries. There had also been reports of animals behaving strangely just before the tsunami. But humans, the socalled paragons of the animal kingdom, were not alert to these signals.